Flexible Lead-Free BiFeO3/PDMS-Based Nanogenerator as Piezoelectric Energy Harvester - Ren, Xiaohu; Fan, Huiqing; Zhao, Yuwei; Liu, Zhiyong (ACS applied materials & interfaces, 2016)
Perovskite ferroelectric BiFeO3 has been extensively researched in many application fields, but has rarely been investigated for the energy conversion of tiny mechanical motions in electricity in spite of its large theoretical remnant polarization. Here we demonstrate the fabrication of a flexible piezoelectric nanogenerator based on BiFeO3 nanoparticles (NPs), which were synthesized using a sol–gel process. The BiFeO3 NPs–PDMS composite device exhibits an output open circuit voltage of ∼3 V and short circuit current of ∼250 nA under repeated hand pressing. The output generation mechanism from the PNG is discussed on the basis of the alignment of electric dipoles in the composite film. It is demonstrated that the output power from the PNG can directly drive the light-emitting diode (LED) and charge capacitor. These results demonstrate that BiFeO3 nanomaterials have the potential for large-scale lead-free piezoelectric nanogenerator applications.